2022
DOI: 10.1073/pnas.2122770119
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule investigations of single-chain cellulose biosynthesis

Abstract: Cellulose biosynthesis in sessile bacterial colonies originates in the membrane-integrated bacterial cellulose synthase (Bcs) AB complex. We utilize optical tweezers to measure single-strand cellulose biosynthesis by BcsAB from Rhodobacter sphaeroides . Synthesis depends on uridine diphosphate glucose, Mg 2+ , and cyclic diguanosine monophosphate, with the last displaying a retention time of ∼80 min. Below a stall force of 12.7 pN, biosynthesis is relatively inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…S1g). Similar biosynthesis rates have recently been reported for cellulose synthase [14]. Monitoring the length distribution of the synthesized HA under these substrate conditions (one limiting, the other in excess) shows increasing HA lengths up to a substrate concentration of 2.5 mM (Fig.…”
Section: Xl-has-1 Synthesizes Ha Polymers In a Megadalton Size Rangesupporting
confidence: 85%
See 1 more Smart Citation
“…S1g). Similar biosynthesis rates have recently been reported for cellulose synthase [14]. Monitoring the length distribution of the synthesized HA under these substrate conditions (one limiting, the other in excess) shows increasing HA lengths up to a substrate concentration of 2.5 mM (Fig.…”
Section: Xl-has-1 Synthesizes Ha Polymers In a Megadalton Size Rangesupporting
confidence: 85%
“…Quantification of Cv-HAS activity followed a similar workflow. Protein concentrations in CvHAS IMVs were normalized as described previously [14]. Reaction buffer consisted of 40 mM TrisHCl pH 7.5, 75 mM NaCl, 20 mM MnCl2, 0.5 mM TCEP, 5 mM UDP-GlcNAc, 5 mM UDP-GlcA and 0.01 μCi/μL [ 3 H]-UDP-GlcNAc.…”
Section: Quantification Of Has Activity By Scintillation Countingmentioning
confidence: 99%
“…Interestingly, plant cellulose synthases also had kcat in a similar range as that of G. hansenii [35,37,38], meaning they also have lower values than that of R. sphaeroides. It is difficult to assess whether the plant CesAs are slower in adding the substrate than R. sphaeroides since a recent study involving cellulose biosynthesis at a single-molecule level shows an addition of glucose every 2.5 secs at room temperature [39]. Such state-of-the-art methods may be required to determine the exact catalytic efficiency and turnover rate of the plant CesAs.…”
Section: Reconstituted Cesa8 Shows a Higher Substrate Affinity Compar...mentioning
confidence: 99%
“…This has been performed in a membranemimicking environment by the use of nanodiscs, the protein embedded in a phospholipid bilayer surrounded by a membrane scaffold protein (MSP). 35 This strategy to study membrane proteins with optical tweezers has only been reported once to date, 36 whereas the unfolding and interactions of a membrane protein in nanodiscs have not been studied before. By introducing a single point mutation, K521C, both SBDs of the homodimer are probed simultaneously in pulling experiments to uncover unfolding transitions and potential interactions.…”
Section: Introductionmentioning
confidence: 99%